Boundary Value Problems for Composite Type Systems of Second Order Partial Differential Equations (Journal of Partial Differential Equations, 1993)
Doundary value problems for composite systems of partial differential equations are investigated in this paper. The uniqueness and existence of claasical solutions and generalized solutions are studied.
Keywords: Composite system; boundary value problem; Fourier method; classical solution; generalized solution